(Un)safe spaces, affective labour and perceived health among people with trans experiences living in Sweden. Issue 8 (3rd August 2019) - Linander, Ida; Goicolea, Isabel; Alm, Erika; Hammarström, Anne; Harryson, Lisa
Abstract: Lack of safe space has been connected to ill health among people with trans experiences. This study analyses trans people's experiences of being in public, semi-public and community spaces using the analytical concept of safety/unsafety in relation to perceived health. The analytic framework draws on the concepts of cisgenderism, orientation, lines and comfort. The material analysed consisted of 18 individual interviews with people with trans experiences, which were analysed using constructivist thematic analysis. The analysis resulted in the identification of three themes: straightening devices creating limited living space, orienting oneself in (cis)gendered spaces and creating safer (?) community spaces for healing. Experiences of unsafety ranged from incidents and fear of different kinds of violence in public and semi-public spaces to the lack of a transpolitically informed agenda in, for example, feminist spaces. Safer spaces helped participants to feel a sense of belonging, to share their experiences and to heal. Experiences of unsafety and discomfort are important as they will help us to understand the health situations of people with trans experiences. It is important to facilitate the creation of safer spaces to improve the health of members of this group.